Morrer para nascer travesti: performatividades, escolaridade e a pedagogia da intolerência - Acosta, Tássio (Universidade Federal de São Carlos, 2016)
This study analyses the narratives of the experiences had in school by six transvestites from the city of Sorocaba (countryside of the State of São Paulo) having the queer perspective as analytic inspiration for understanding that the discriminations suffered while in school were focused on maintaining the heteronormativity as disciplinary process. When considering the school as a device to maintain the relations focused on power, their gender expressions were vital for this process to be put to practice in an even more intensified manner – sometimes they were made invisible, while others they were given extreme visibility in order to serve as examples of "abnormal" behavior/identity. The most recurrent disciplinary devices defined by gender during such narratives were related to the birth name, the school uniform, the collective restrooms and Physical Education classes. Several attempts of resisting such devices were observed, in addition to strategies aimed at “compensating” discrimination, such as being the best student in some subjects, being good at sports or seeking interpersonal relationships with other “rebellious” students in order to obtain acceptance and/or strength before normalizations. The symbolic violence was present by the use of sexist nicknames, both by students and teachers, who many times have endorsed such anti-social and violent behaviors in their most diverse forms against the interviewees. They were blamed, both by the teaching and managing entities, for the violence suffered. When the issue of “race” was inserted in the scenario – as in the case of two black interviewees – the violence suffered by them would become even more evident. The acknowledgement of their precariousness and vulnerability is necessary to foment the creation of specific public policies, by means of affirmative actions, aiming at removing them from the fringes of society and making their lives more livable.
Die to be bom a transvestite: performativity, education and tlje pedagogy of intolerance
Keywords: Travestis; Transvestites; Transfobia; Transphobia; Identidade de gênero na educação; Gender identity in education; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO